Rancang Bangun Sistem Penjualan dengan Metodologi Berorientasi Obyek (Studi Kasus: PT. Bangsawan Cyberindo) - Deni Kuswoyo (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
In the current era of globalization, information and computer technology has a decisive role in a business competition. PT. Bangsawan Cyberindo is a company engaged in the sale of goods and services of information technology. Currently, the sales information system used has not maximized the use of the computer yet that there are still many activities using manual recording system. This manual recording makes sales staff have difficulty in recording the goods selling data because the data acquired are less accurate, slow and incomplete, leading to delays in reporting goods selling data. Besides, the accounting process has not been well conducted, so that important reports describing financial statements are not available yet. Therefore, through this paper, the author proposes the utilization of design of sales information system covering sales activities in PT.Bangsawan Cyberindo. This information system makes the data recording easier and supports the smooth running of sales information system. Then, the system also eases the report printing process based on the expected periods so that the information can be easily, quickly and accurately found and the errors can be minimized. The system is designed adopting object-oriented methodology and is implemented using programming language Visual Studio 2005 and MS Access as its database.